Perbandingan Metodologi SDLC Waterfall dan Agile Dalam Rencana Pengembangan Sistem Informasi Kepatuhan - Burhani, Irfan; Juwari, Juwari; Soderi, Ahmad; Diantoro, Karno (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
The development of compliance information systems plays a strategic role in the banking industry, particularly in ensuring that every operational activity adheres to continuously evolving regulations. Bank Syariah Indonesia faces challenges in determining the most effective and efficient system development methodology to be applied in developing compliance information systems. This study aims to compare two system development methodologies: Waterfall and Agile. A qualitative approach was used, with data collected through interviews and questionnaires distributed to 60 respondents, determined using the Slovin formula with a 2% margin of error. The results show that 83% of respondents consider the Agile method to be more flexible in responding to regulatory changes due to its iterative nature, ability to adjust backlogs, and open team communication. On the other hand, Waterfall is still considered relevant for projects that require detailed documentation and a strict structure. The main weakness of Waterfall lies in its limited ability to adapt to changes that arise at the end of the development cycle. This study recommends a Hybrid approach that combines the flexibility of Agile and the structured nature of Waterfall, to ensure the development of compliance information systems that are adaptive, well-documented, and aligned with complex and dynamic regulatory requirements.